Microwave Sterilizer - Ho, Kuen Seng (Universiti Sains Malaysia, 2017)
The studies of the effect of microwave irradiation on biological effects and chemi-cals properties have been widely conducted over the years. The viability of microwave ster-ilization is one of the study that has been going on for years. However, most of the studies and researches involve the use of a conventional microwave oven which do not provide ap-propriate features to aid them in their studies. Development of a microwave sterilizer sys-tem with a computer graphical user interface (GUI) are involved in this project. A conven-tional microwave oven is modified with Arduino Uno as the controller to achieve flexible treatment duration settings and temperature monitoring. An infrared (IR) thermopile sensor is integrated to the system to monitor the temperature of the sample within the microwave chamber. The effectiveness of microwave sterilization on nipa palm sap is studied in this project as well using the developed microwave sterilization system. Spread plate technique is used to calculate the colony forming unit (CFU) and the results are compared to verify the effectiveness of microwave sterilization. The microwave sterilizer system developed has a user-friendly GUI to control the treatment duration and temperature monitoring. The system is capable of generating a thermal profile for the treated sample and threshold tem-perature can be set for the treatment. The experiment has shown that microwave radiation is effective and viable in the sterilization of sap of Nypa Fruticans. The microwave steriliza-tion system developed is proved to be helpful throughout the experiment.